Observation of Spontaneous C=C Bond Breaking in the Reaction between Atomic Boron and Ethylene in Solid Neon. (30th May 2016) - Jian, Jiwen; Lin, Hailu; Luo, Mingbiao; Chen, Mohua; Zhou, Mingfei
Abstract: A ground‐state boron atom inserts into the C=C bond of ethylene to spontaneously form the allene‐like compound H2 CBCH2 on annealing in solid neon. This compound can further isomerize to the propyne‐like HCBCH3 isomer under UV light excitation. The observation of this unique spontaneous C=C bond insertion reaction is consistent with theoretical predictions that the reaction is thermodynamically exothermic and kinetically facile. This work demonstrates that the stronger C=C bond, rather than the less inert C−H bond, can be broken to form organoboron species from the reaction of a boron atom with ethylene even at cryogenic temperatures.